Pharmacist’s perceived barriers in providing counseling services to ambulatory type 2 diabetes mellitus patients: A qualitative phenomenological study in Bali, Indonesia - Made Krisna Adi Jaya,, Fita Rahmawati, Nanang Munif Yasin, Zullies Ikawati (Journal of Applied Pharmaceutical Science, 2025)
Type 2 diabetes mellitus (T2DM) is one of the chronic diseases that requires long-term medical control. Ambulatory T2DM patients are at risk of experiencing adverse events. The safety of patients undergoing therapy is the responsibility of health workers. Pharmacists are essentially professionals who can contribute to overseeing patient safety. Pharmacist counseling activities for T2DM patients as preventive and promotive efforts are considered very important and beneficial. Pharmacist counseling services for ambulatory diabetes mellitus patients do not work because there are barriers to implementing them. This study aimed to map the pharmacist’s perceived barriers in providing counseling services to ambulatory T2DM patients. A qualitative phenomenological study was carried out as a study design. Pharmacists were interviewed to obtain an overview of the barriers faced while providing counseling services to T2DM patients. The data were processed through verbatim transcription, coding, theming, and synthesis of the thematic framework. There were six categories of barriers found, including personal-perceived barriers, barriers from patients, interprofessional barriers, barriers due to health facility policies, barriers due to health facility infrastructure, and barriers due to government policies and regulations. The barriers have been successfully mapped. Strategic efforts need to be made to overcome these barriers.
Keywords: Ambulatory, barrier, counseling service, pharmacist, qualitative phenomenological study, type 2 diabetes mellitus